2021
DOI: 10.38015/sbyy.772107
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bilgiler Son Sınıf Öğretmen Adaylarının Sosyal Bilgilere Bakışı

Abstract: Bu araştırmanın amacı sosyal bilgiler son sınıf öğretmen adaylarının sosyal bilgilere bakış açısını ortaya koymaktır. Araştırmanın çalışma grubunu, 2018-2019 eğitim öğretim döneminde bir devlet üniversitesinin eğitim fakültesi sosyal bilgiler eğitimi son sınıfında öğrenim gören 53 öğretmen adayı oluşturmuştur. Nitel araştırma yöntemi benimsenen bu çalışma, olgu bilim (fenomonoloji) modelinde desenlenmiştir. Bu çalışmanın verileri uzman görüşleri doğrultusunda araştırmacılar tarafından oluşturulmuş 8 açık uçlu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…However, it is found that the pre-service social studies teachers are less satisfied with the image of their study field than the other participants. In the research conducted by Akhan and Mert (2021), pre-service social studies teachers think that their fields are not given the necessary value. For this reason, this may be due to the thoughts of pre-service social studies teachers that their fields are not given the necessary value.…”
Section: Factorsmentioning
confidence: 99%
“…However, it is found that the pre-service social studies teachers are less satisfied with the image of their study field than the other participants. In the research conducted by Akhan and Mert (2021), pre-service social studies teachers think that their fields are not given the necessary value. For this reason, this may be due to the thoughts of pre-service social studies teachers that their fields are not given the necessary value.…”
Section: Factorsmentioning
confidence: 99%